GENDER DIFFERENCES IN SELF-ESTIMATES OF MULTIPLE INTELLIGENCES AMONG LEARNERS OF ENGLISH - Abbas Zare-ee; Zuraidah Mohd Don; Gerry Knowles; Iman Tohidian (Informascope, 2015)
According to Howard Gardner, human intellectual ability cannot be measured by a unitary concept of general intelligence, and the performance of cognitive tasks draws on different types of intelligence, including linguistic, logical-mathematical, musical, spatial, bodily-kinaesthetic, interpersonal, intrapersonal, natural, and existential. Despite the lack of adequate empirical support and recent doubts raised about its validity, this view of multiple intelligences has been extensively employed for the characterization of learners and the development of tasks for language teaching and learning. Whereas gender differences in the learning and use of language have been extensively researched, context-specific information on gender differences in different domains of multiple intelligences has not been seriously examined. The survey reported here is based on the hypothesis that multiple intelligences vary not only at the individual level, but also in the case of gender at a cultural level, and uses Mckenzie's Multiple Intelligences Survey to explore possible gender differences in Gardner's intelligences. Questionnaire data relating to each of the nine intelligences was elicited from 300 undergraduate volunteers studying English at the University of Kashan in central Iran. The questionnaire included 90 statements and 10 items on each intelligence, and was used to identify the intelligence profile of the participants according to their own self-estimates. The scores for each intelligence type were calculated, analyzed and compared across genders. The results of the study showed that in contrast to the trend observed in previous research, female learners tended to rate themselves higher on most intelligences and their means were significantly higher than those of male learners in the areas of naturalistic and existential intelligences. The findings have both theoretical and practical implications not only for the reconsideration of previous claims that males rate themselves more highly with regard to intelligences, but also for the MI theory itself.